Systemic Challenges for Primary Teachers - JHA, SANJEEV KUMAR (THE PRIMARY TEACHER, 2014)
Presently the training of teachers, both prospective and practicing, is very weak. One of the main factors contributing to this situation is that teachers are trained in a way that students in schools are taught. This is based on the premise that learning behaviour of both adults and students is the same. This is an erroneous assumption. There are researches which now reflect that children and adults learn in fundamentally different ways. There are now two sciences – Pedagogy and Andragogy. The former is the art and science of helping children to learn and the latter stands for art and science of helping adults to learn. Malcolm Knowles, an American practitioner and theorist of adult education is the pioneer of andragogy